PENGARUH LAYANAN BIMBINGAN KARIER TERHADAP MINAT KARIER SISWA KELAS XI SMA MUTIARA 2 BANDUNG - Rayni, Selma; Siddik, Riesa Rismawati; Rohaeti, Euis Eti (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2024)
This study aims to determine the effect of career guidance services on career interests of class XI students SMA Mutiara 2 Bandung. This research uses the research method of counseling guidance action (PTBK) with the subject of research as many as  20 students of clas XI SMA Mutiara 2 Bandung. The method of data collaction using observation, interviews, and research documentation. Consists of 2 cycles. While the data analysis technique used descriptive analytical analysis. The process of data analysis begins by examining all the data obtained, either though interviews or observations. Then described by using percentage analysis. The Results of the study indicate that in the initial conditions,students’ career intrests are still in the “not good” category, in the first cycle there are indicators that have increased in the “very good” category, namely the indicator of introduction to the world of work with descriptors knowing the world of work, with percentage of by 75% of the 15 students. While in the second cycle all indicators have increases by getting the “very good” category with a percentage of >80% on each indicator from 18 students. Thus, it can be concluded that career guidance services can affect the career interests of students in class XI SMA Muttiara 2 Bandung.